Therapeutic Communication Techniques in Islamic Counseling Guidance Services for Handling Drug Abuse - Cucu Siti Rodiah; Isep Zaenal Arifin; Hajir Tajiri (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research also wants to identify related challenges and opportunities in implementing this technique. This type of research is field research which was carried out using descriptive qualitative research methods to obtain objective and in-depth qualitative data about Therapeutic Communication Techniques in Islamic Counseling Guidance (BKI) for Handling Drug Abuse among High School students. The research data is presented descriptively so that the research findings are presented sequentially, in detail and in depth. The results of this research show that therapeutic communication techniques in Islamic Counseling (BKI) for handling drug abuse can have a positive impact on the students involved, so that they feel more comfortable to open up about sharing their experiences regarding drug abuse without feeling intimidated and Terjudim, apart from that, is also able to be an alternative that can provide motivation, cure and provide solutions for students to escape the trap of drugs. This research concludes that the application of therapeutic communication techniques in Islamic counseling guidance is very effective in dealing with drug abuse among students at Senior Highschool. However, further training is needed for counselors or guidance and counseling teachers in schools so that they can implement this technique optimally and involve the school community as a whole to create a culture of preventing and controlling drug abuse.